Influence of nursing competence, leadership, team coordination, and resources on flood disaster nursing effectiveness - Johansen Hutajulu; Ivan Elisabeth Purba; Henny Syapitri; Tanti Yosepha Ompusunggu (Nursing and Health Sciences Journal (NHSJ), 2026)
Flood disasters represent a prevalent global hazard that imposes significant strain on healthcare systems, necessitating robust nursing management to ensure timely and effective service delivery. This study examined the influence of nursing competence, leadership, team coordination, and resource availability on disaster nursing management effectiveness during flood responses. Using a quantitative cross-sectional design, data were collected from 96 nurses with direct flood response experience using a validated, structured questionnaire. Multiple linear regression analysis was employed to assess the individual and simultaneous effects of the independent variables. Results demonstrated that nursing competence, leadership, team coordination, and resource availability all exerted a positive and significant influence on management effectiveness (p < 0.05). Collectively, these variables accounted for 55.6% of the variance in effectiveness, with team coordination and leadership as the strongest predictors. These findings underscore that optimal disaster nursing management relies on an integrated approach combining individual competency with strong leadership structures, cohesive teamwork, and adequate logistical support. Consequently, disaster preparedness strategies should prioritize leadership development and coordinated team protocols alongside clinical training to enhance resilience in flood-prone regions.